Strong support for Rensch's rule in an American clade of lizards (Teiidae and Gymnophtalmidae) and a paradox of the largest tejus - Frýdlová, Petra; Frynta, Daniel (Die Naturwissenschaften, 2015)
Rensch's rule predicts an allometric relationship between male and female body size stating that the sexual size dimorphism (SSD) increases with body size in male-larger taxa and decreases in female-larger taxa in groups of related species. It means that the relationship between the male and female body size is hyperallometric, i.e., the allometric exponent of this relationship exceeds the unity. We explored the relationship between the male and female body size in a New World clade of lizards consisting of sister families Teiidae and Gymnophthalmidae, which exhibit a great variation in both their adult body sizes and SSD. All our estimates of the reduced major axis regression slopes ranged from 1.067 to 1.229 and clearly followed a pattern consistent with the Rensch's rule. Despite a clear general trend, giant species from the subfamily Tupinambinae show paradoxically only poor SSD. The cases of extreme male-larger SSD were found in species of moderate body size belonging to the genera Ameiva and Cnemidophorus. The abovementioned deviations from the hyperallometric relationship between the male and female body size are surprising and require further examination.
Keywords: pohlavní dimorfismus; Body Size; Female; Lizards; Animals; ženské pohlaví; Střední Amerika; mužské pohlaví; Central America; Male; velikost těla; Phylogeny; zvířata; fylogeneze; Sex Characteristics; ještěři